Clinical Inertia A Critique of Medical Reason - Reach, Gérard (Springer International Publishing : Imprint: Springer, 2015)
Clinical practice guidelines were initially developed within the context of evidence-based medicine with the goal of putting medical research findings into practice. However, physicians do not always follow them, even when they seem to apply to the particular patient they have to treat. This phenomenon, known as clinical inertia, represents a significant obstacle to the efficiency of care and a major public health problem, the extent of which is demonstrated in this book. An analysis of its causes shows that it stems from a discrepancy between the objective, essentially statistical nature of evidence-based medicine on the one hand and the physician's own complex, subjective view (referred to here as "medical reason") on the other. This book proposes a critique of medical reason that may help to reconcile the principles of evidence-based medicine and individual practice. The author is a diabetologist and Professor of Endocrinology, Diabetology and Metabolic Diseases at Paris 13 University. He has authored several books, including one to be published by Springer (Philosophy and Medicine series) under the title: The Mental Mechanisms of Patient Adherence to Long Term Therapies, Mind and Care.